Microsoft Azure Data Engineer Associate (DP-203) Cert Prep: 3 Design and Implement Data Security by Microsoft Press. - Warner, Tim; Press, Microsoft (linkedin.com, 2023)
Explore the fundamental concepts and skills required to design and implement data security to pass the Microsoft Azure Data Engineer Associate (DP-203) certification exam.